Ekskalasi Pondok Pesantren Daarul Khair Di Muara Jaya Kecamatan Kotabumi Lampung Utara Pada Tahun 1991-2003 - Erik Rahmana Putra; Syarifuddin Syarifuddin (Fakultas Adab dan Humaniora UIN Raden Fatah, 2022)
In this study, researchers examined the background of the establishment of the Daarul Khair Islamic Boarding School and the development of the Daarul Khair Islamic Boarding School in Muara Jaya, Kotabumi District, North Lampung Regency in 1991-2003. The method used in this study is the historical method which has four stages, namely: first, heuristics that are useful for finding information or sources regarding research, secondly source criticism which is useful for testing the authenticity and credibility of source materials, third is interpretation. , namely interpreting the sources obtained and the last is historiography, namely writing a report on the final results of the study. The results showed that the Daarul Khair Islamic Boarding School was a boarding school that was established in Muara Jaya, Kotabumi District, North Lampung Regency, this Islamic Boarding School was built on the basis of wanting to spread Islamic teachings for the safety of the people in 1991. This can be seen from 1991-2003 which was marked by the development of several aspects, namely: students, teachers, pesantren curriculum, and facilities and infrastructure. Keyword: Islamic boarding school, Daarul Khair, Kotabumi District